2014
DOI: 10.3892/or.2014.3186
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTAIR is a powerful predictor of metastasis and poor prognosis and is associated with epithelial-mesenchymal transition in colon cancer

Abstract: Abstract. Colon cancer is one of the most frequently diagnosed cancer and the third most fatal malignancy worldwide. HOTAIR, a cancer-associated long non-coding RNA (lncRNA), is a powerful biomarker of metastasis and poor prognosis in a diverse group of cancers. Nevertheless, an understanding of how HOTAIR is involved in colon cancer progression is limited. In the present study, we hypothesized that HOTAIR plays a crucial role in colon cancer development. We evaluated the expression of HOTAIR in 120 colon canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(155 citation statements)
references
References 24 publications
10
144
1
Order By: Relevance
“…The 3' end of HOTAIR interacts with lysine-specific histone demethylase 1A (22). Furthermore, recent studies have reported that HOTAIR is highly expressed and associated with poor prognosis in a number of types of cancer, including breast cancer, epithelial ovarian cancer, pancreatic cancer, colorectal cancer, non-small-cell lung cancer and endometrial carcinoma (21,(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The 3' end of HOTAIR interacts with lysine-specific histone demethylase 1A (22). Furthermore, recent studies have reported that HOTAIR is highly expressed and associated with poor prognosis in a number of types of cancer, including breast cancer, epithelial ovarian cancer, pancreatic cancer, colorectal cancer, non-small-cell lung cancer and endometrial carcinoma (21,(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer patients with high HOTAIR expression had higher recurrence rates and reduced metastasis-free and overall survival compared with those with low HOTAIR expression. Further investigation revealed that HOTAIR increased the expression of E-cadherin and decreased the expression of vimentin and MMP9 [75]. Svoboda et al demonstrated that HOTAIR expression was increased in primary tumors and blood of CRC patients, and its levels in tumors were associated with higher mortality of patients, suggesting that HOTAIR blood levels might serve as a potential surrogate prognostic marker in sporadic CRC [76].…”
Section: Hotairmentioning
confidence: 99%
“…Multiple protein markers are associated with EMT, including ZEB1, ZEB2, SNAI1, SNAI2, Vimentin, E-cadherin, and N-cadherin (Kalluri & Weinberg, 2009). HOTAIR has been associated with an increase in EMT and cancerous proliferation via suppression of E-cadherin, an epithelial marker, and alteration of nuclear organization to that of a more invasive mesenchymal cell (Wu et al, 2014). An important regulator of EMT, the SNAIL protein, is also shown to associate with HOTAIR in the nucleus and direct the methylation of targets to further promote EMT; again, in this situation HOTAIR acts as a scaffold bringing together SNAIL and the EZH2 subunit of PRC2 for targeted methylation (Battistelli et al, 2016).…”
Section: Hotair In Cellular Aberrancymentioning
confidence: 99%